The relationship between serum leptin and VO2max levels in pre-puberty swimmer girls: effect of acute exercise - Güllü, Esin; Güllü, Abdullah; Düzova, Halil; Özgör, Bilge; Kilinç, Evren; Akçinar, Faruk (Progress in Nutrition, 2020)
Objective: The aim of this study was to determine the relationship between serum leptin (SL) level, which is the sensor of changes in energy intake and consumption, and maximal oxygen consumption (VO2max) level in pre-puberty swimmer girls. Methods: Voluntary participants were divided into swimmer group (n: 16) and the control group (n: 15). Bruce protocol was used for acute exercise effect. Body composition, VO2max and SL concentrations of the study group were measured before and after acute exercise. The paired-samples t-test and independent samples t-test were used for intra- and inter-group comparisons. The linear relations between the VO2max and SL levels were determined by Pearson correlation coefficient. The level of significance was used at 0.05. Results: There was a significant difference between the SL level and test stage, test duration, HR of test-end, and VO2max variables in both groups (p